DETERMINATION OPTIMAL DISTRIBUTION OF LABOR POTENTIAL OF REGION METHODS OF MATHEMATICAL MODELING - Irina Zaitseva; Alla Nemova (Вестник Северо-Кавказского федерального университета)
The authors of a mathematical model, which is a nonlinear programming problem. Statistical data on the labor force and economic indicators used in the mathematical model for the optimal distribution of the region S labor potential. The model parameters are the total amount of investment per worker in industry and the profit that it brings the industry, which are calculated according to the statistics. The objective function in the model is the so-called «utility function». The process of solving the problem of nonlinear programming is automated with the help of the developed software product. Graphical user interface software for the mathematical model allows to visualize the optimal allocation of labor potential categories.